Strengthening Early Literacy through Collage Learning Based on Tri-N Local Wisdom: Case Study in Elementary Schools - Lina Setyawati; Insanul Qisti Barriyah; Akbar Al Masjid; Sutrisna Wibawa (Jurnal Ilmiah Sekolah Dasar, 2025)
Early literacy is a fundamental foundation in children’s cognitive development that plays a crucial role in shaping reading and writing skills in primary education. However, literacy learning practices in elementary schools tend to remain conventional and have not widely integrated local wisdom that can enrich students’ learning experiences. This study aims to analyze the strengthening of early literacy through collage-based learning grounded in the Tri-N  local wisdom approach, namely Niteni, Nirokke, and Nambahi, in elementary school learning. This research employed a qualitative approach with a case study design. The research subjects consisted of elementary school teachers and students involved in Tri-N -based collage learning activities. Data were collected through observations, interviews, and analysis of learning documents, using observation guidelines, interview guides, and document analysis sheets as research instruments. Data were analyzed using the interactive analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through technique and source triangulation as well as member checking. The results indicate that Tri-N -based collage learning can enhance students’ early literacy skills, particularly in reading, writing, creativity, and active engagement in the learning process. The integration of local wisdom in collage media also helps students understand cultural values and appreciate diversity. The implications of this study suggest that integrating creative activities based on local wisdom can serve as an effective pedagogical strategy to develop contextual early literacy and can be used as a reference for developing more meaningful and sustainable literacy learning models in elementary schools.